The impact of oil price and its impact on public finances of Colombia (2015)
Hydrocarbons in Colombia play a very important role because with the passing of the years they were becoming one of the main engines for boosting economic growth of the Colombian state. Since its discovery was the target of major foreign oil companies who saw a major source of wealth, which took shape under the concessions granted by the government to foreign companies in this resource; then the state created a responsible public company to regularize and exploit this precious natural resource, at this point the government has underpinned much of their income in taxes from sales of crude oil, this is how the Colombian state depends largely on these income for sustenance disappeared that would create a huge tax gap difficult to replace with another export product, then a summary of the most important moments in the history of this precious mining